GENOMIC FACTORS (TOLL-LIKE RECEPTORS GENES) IN DEVELOPMENT OF ATHEROSCLEROSIS AND ITS CLINICAL MANIFESTATIONS - I. I. Zhidkova; A. V. Ponasenko; M. V. Khutornaya; A. G. Kutikhin; O. L. Barbarash (Медицинская иммунология)
Development of atherosclerosis and its clinical manifestations, i.e. unstable angina, myocardial infarction, and ischemic stroke, is largely determined by a genetic inheritance, particularly inherited variation of the genes encoding Toll-like receptors (TLRs), a major effector of innate immune system. Polymorphisms of the TLR genes may affect vascular inflammation, as well as plaque formation and its stability. Miriades of immune cells and bioactive substances are involved into pathogenesis of atherosclerosis. They exert different effects upon vascular wall and participate in development of universal inflammatory response. Local inflammatory reaction underlyes atherosclerotic plaque destabilization and endothelial dysfunction. This response is associated with TLR activation and induced synthesis of proinflammatory cytokines. Here we review the literature on the role of inherited variations within the TLR genes in the development and progression of atherosclerosis and its complications. Moreoxer, we conclude that a search for genomic markers of atherosclerosis, e.g., TLR gene polymorphisms, may be applied in personalized cardiovascular medicine, in order to predict clinical course and evolution of the disorder, like as to perform prophylactic measures aimed for prevention of the disease progression.